PENERAPAN INSTRUMEN SUKARELA DAN COMMAND AND CONTROL DALAM PENATAAN LINGKUNGAN USAHA/KEGIATAN PERHOTELAN - Chrisyela Sinaga (Universitas Muhammadiyah Mataram, 2021)
ABSTRACTEnvironmental problems have become a global issue, not only a problem for common industries like mineral and mining, but also have penetrated into the tourism sector. The hospitality industry contributes wastewater from its activities or businesses that have the large potential to pollute the environment if preventive measures are not taken. The huge environmental management costs and the lack of entrepreneur commitment are some of the reasons for hotels not to carry out wastewater treatment, so that environmental pollution due to hotel activities cannot be avoided and becomes uncontrollable. Smart regulation is needed to organize the environment in hospitality business activities in a flexible, imaginative and innovative manner. This research aims to analyze environmental compliance policy mixes in hospitality activity. This research is normative legal research methods with the conceptual approach and statute approach. It is analyzed qualitatively. The results of the research showed that in environmental compliance of the hospitality activity, policy mixes can be applied between voluntary instruments and Command and Control instrument that could carried out through PROPER and the need for hospitality activities to be re-incorporated into PROPER participation.Keywords: Environmental Compliance Instrument; Smart Regulation; Policy Mixes, Accommodations Waste. ABSTRAKPermasalahan lingkungan hidup kini telah menjadi isu global, tidak hanya menjadi permasalahan bagi industri-industri raksasa seperti mineral dan tambang, namun juga telah merambah sektor pariwisata. Industri perhotelan menyumbang air limbah dari kegiatan atau usahanya yang berpotensi besar mencemari lingkungan apabila tidak dilakukan tindakan pencegahan. Biaya pengelolaan lingkungan yang sangat besar dan kurangnya komitmen pengusaha menjadi alasan bagi pengelola hotel untuk tidak melakukan pengolahan air limbah, sehingga pencemaran lingkungan akibat kegiatan hotel tidak dapat dihindari dan menjadi tidak terkendali. Diperlukan smart regulation untuk menata lingkungan dalam kegiatan usaha perhotelan secara fleksibel, imaginatif dan inovatif. Penelitian ini bertujuan untuk menganalisa pilihan kombinasi instrumen penataan lingkungan pada kegiatan perhotelan. Penelitian ini merupakan penelitian normatif dengan pendekatan konsep dan pendekatan perundang-undangan yang dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa dalam penataan lingkungan kegiatan perhotelan dapat diterapkan policy mixes antara instrumen sukarela dengan Command and Control yang dapat dilakukan melalui PROPER serta perlunya kegiatan perhotelan dimasukkan kembali dalam keikutsertaan PROPER.